Business Process Reengineering to Improve Supply Chain Management at Batik Semarang 16 Through Implementation of ERP Odoo - Bayu Setyo Nugroho; Sri Marhaeni Salsiyah; Sugiyanta; Anandike Cita Kumala; Idha Rizqi Pratiwi; Ranira Salma Edza Fabillah; Arumsari, Vita (Indonesian Journal of Information Systems, 2024)
This study aims to design an improvement in the Supply Chain Management using the ERP Odoo application. This research starts from conducting field studies on the research object, designing the required system, prototyping, testing, and implementation. The methodology used is RND Borg and Gall Method approach to reach the right model in making business models for reengineering ERP implementation in small and medium enterprises. As a result, the business processes create using Odoo, is way more efficient because all business activities can be integrated with each other so that there is an automation of changing the working status of the product so there is no need to check manually. Finally, testing has been done to see how well the system is.